Absorbing perfections : Kabbalah and interpretation - Idel, Moshe, 1947- (Yale University Press, 2002)
In this wide-ranging discussion of Kabbalah - from the mystical trends of mediaeval Judaism to modern Hasidism - this book considers different visions of the nature of the sacred text and of the methods to interpret it. It takes as a starting point the fact that the post-biblical Jewish world lost its geographical centre with the destruction of the temple and so was left with a textual centre, the Holy Book. The author argues that a text-oriented religion produced language-centred forms of mysticism. Against this background, he demonstrates how various Jewish mystics amplified the content of the Scriptures so as to include everything: the world, or God, for example.
Keywords: Bible. -- Pentateuch -- Criticism, interpretation, etc., Jewish.; Bible -- A.T. -- Pentateuque -- Critique, interprétation, etc. juives.; Bible. -- Pentateuch; Cabala -- History.; Kabbale -- Histoire.; RELIGION -- Judaism -- Kabbalah & Mysticism.; RELIGION -- Judaism -- Sacred Writings.; Cabala; Jodendom.; Mystiek.; Kabbala.; History